Biochemical and Environmental Bioprocessing : Challenges and Developments. - Jerold, M.; Sivasubramanian, V. (Milton : CRC Press LLC, 2019)
The rapid growth of industries has resulted in the generation of high volume of solid and liquid waste. Today, there is a need of Clean and Green technology for the sustainable waste management. Biochemical and Environmental Bioprocessing: Challenges and Developments explore the State-of-art green technologies to manage the waste and to recover value added products. Microbes play an important role in the bioremediation. Bioprocess engineering an interdisciplinary connects the Science and Technology. The bioconversion and bioremediation is essentially required for the management of various hazardous substances in the environment. This book will give an intensive knowledge on the application of Biochemical and Bioprocess technologies for the eco-friendly management of pollution. This book serves as a fundamental to the students, researchers, academicians and Engineers working in the area of Environmental Bioremediation and in the exploration of various bioproducts from waste. Features Reviews various biological methods for the treatment of effluents from Industries by using biomass and biopolymers. Highlights the applications of various bioreactors like Anaerobic Sequential Batch Reactor, Continuously stirred anaerobic digester, Up-flow anaerobic sludge blanket reactor, Fluidized and expanded bed reactors. Presents the cultivation of algae in Open Pond, Closed loop System, and Photo-bioreactors for bioenergy production. Discusses the intensified and integrated biorefinery approach by Microwave Irradiation, Pyrolysis, Acoustic cavitation, Hydrodynamic cavitation, Electron beam irradiation, High pressure Autoclave reactor, Steam explosion and photochemical oxidation. Outlines the usage of microbial fuel cell (MFC) for the production bioelectricity generation in different modules Tubular MFC, Stacked MFC, Separate electrode modules Cutting edge research of synthesis of biogenic nanoparticles and Pigments by green route for the health care and environment management.
Biosorption-an elective strategy for wastewater treatment: An eco-friendly approach, Recent Advancements and Perspectives on Biological Degradation of Azo Dye, Performance analysis of anaerobic digestion of textile dyeing industry effluent in a modified sequential batch reactor, Waste sea shells for biodiesel production -- Current status and future perspective, AN INTENSIFIED AND INTEGRATED BIOREFINARY APPROACH FOR BIOFUEL PRODUCTION, Hydrothermal carbonization for valorisation of ricehusk, Production of biofuels from algal biomass, Diffusion limitations in biocatalytic reactions: Challenges and Solutions, Recent advancements and applications of nanotechnology inexpelling heavy metal contaminants from wastewater, Organic Flocculation as an Alternative For Wastewater Treatment, Power production in Microbial Fuel Cells (MFC): Recent progress and Future scope, Synthesis, Characterization and Antimicrobial Properties of Cuo Loaded Hydrophobically Modified Chitosans, Fucoxanthin: Biosynthesis, structure, extraction, characteristics and its application
OCLC-licensed vendor bibliographic record.
Keywords: Green chemistry; Biochemical engineering; Bioremediation; Natural products -- Biotechnology; SCIENCE -- Biotechnology; TECHNOLOGY -- Engineering -- Chemical & Biochemical; TECHNOLOGY -- Environmental Engineering & Technology